Personality and Behavioural Characteristics of Dark and Light Narcissism - Petrović, Boban; Međedović, Janko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
Narcissism is one of the Dark traits usually associated with amoral and antisocial dispositions. However, in contrast to the other Dark traits, some aspects of narcissism are connected with socially acceptable aspects of human behaviour. Dark and Light aspects of narcissism were identified by partialling out the variance of narcissism for the variance of psychopathy, Machiavellianism and sadism. Results showed that Dark and Light narcissism differ with respect to relations with HEXACO personality traits (study 1) and antisocial behaviour, schizotypy and unrestricted socio-sexuality (study 3). The results of study 1 were replicated on the clusters of individuals differing in Dark and Light narcissism (study 2). Thus, narcissism encompasses two aspects, one associated with immoral dispositions and the other reflecting a more benign side of human functioning.